2017
DOI: 10.13189/azb.2017.050201
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Environmental Factors for the Prediction of Leaf Rust of Wheat in Sargodha

Abstract: Wheat leaf rust (Puccinia recondite f. sp. tritici) is amongst major wheat diseases occurring in all wheat growing areas of Pakistan. Losses due to the infection by P. recondite f. sp. Tritici have lowered the wheat production potentially in previous years in Pakistan. This problem can be avoided by incorporating resistance against disease in wheat. In the present study eight genotypes/lines were screened and correlated with epidemiological factors i.e. temperature, relative humidity, rainfall and wind speed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
1
7
0
Order By: Relevance
“…Therefore, it is crucial to measure the relationship between epidemiological variables and leaf rust severity to detect its onset early on [ 46 , 47 ]. The present investigation found a significant correlation between epidemiological variables and leaf rust severity (%), which is in line with the findings of [ 10 , 13 ] who showed a significant relationship between leaf rust severity and environmental variables. The leaf rust severity (%) increased when the maximum temperature (17.8–26.8 °C) and minimum temperature (7.91–15.03 °C) increased during both rating seasons.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is crucial to measure the relationship between epidemiological variables and leaf rust severity to detect its onset early on [ 46 , 47 ]. The present investigation found a significant correlation between epidemiological variables and leaf rust severity (%), which is in line with the findings of [ 10 , 13 ] who showed a significant relationship between leaf rust severity and environmental variables. The leaf rust severity (%) increased when the maximum temperature (17.8–26.8 °C) and minimum temperature (7.91–15.03 °C) increased during both rating seasons.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, sufficient precipitation is a prerequisite for the incidence of infection under low-temperature environments. Certain infections may occur when the temperature ranges from 2 °C to 32 °C with the presence of sufficient moisture [ 12 , 13 ]. In their recent study, Smith et al [ 14 ] investigated the impact of weather parameters on the progress of leaf rust.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of epidemiological variables showed that all environmental conditions remained significant against disease development. Temperature (both minimum and maximum) rapidly enhanced the urediniospores intensity at per unit area of infected leaves leading to the production of more spores per day (Milus et al, 2009;Ali et al, 2017). Under high relative humidity, appressoria germination of fungus increased between 4-25 0 C maximum and minimum temperature, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…striiformis, respectively, cause substantial yield losses and socio-economic instability (Rehman et al, 2013;Ali et al, 2017). The diseases develop on susceptible cultivars during suitable environmental conditions.…”
Section: Monitoring Of Leaf Rust and Stripe Rust Virulent Racesmentioning
confidence: 99%